2020
DOI: 10.33448/rsd-v9i2.2067
|View full text |Cite
|
Sign up to set email alerts
|

Comparação de métodos de agrupamentos hierárquicos aglomerativos em indicadores de sustentabilidade em municípios do estado do Pará

Abstract: This study aimed to compare the performance of hierarchical agglomerative clustering methods using a data set composed of several sustainability indicators referring to the municipalities of the state of Pará. As well as determining the number of initial groups to be formed by applying of validity indexes. For the selection of indicators, a check-list of national, regional and local scientific studies addressing the theme of sustainability was carried out. Subsequently, the indicators were standardized due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…Still according to Figure 3, the results showed that Ward's structure was the one that presented the best performance and quality among the agglomerative methods in the dimensions because it presented values closer to 1, this fact was more evident in the general dimension that showed 80% more efficient than the others, and the simple method, which obtained the lowest value, is not indicated, as it has low efficiency, this is due to the fact that this method evaluates the smallest dissimilarity between the objects studied. The CA obtained in this research (0.99) was higher than the study by Crispim et al (2020), in which he obtained CA = 0.94 and equal to that obtained by Roth et al (2016), with CA = 0.99. Thus, the results indicate that this technique is the most appropriate to be used in the database related to sustainability indicators for the municipalities.…”
Section: Resultscontrasting
confidence: 76%
See 4 more Smart Citations
“…Still according to Figure 3, the results showed that Ward's structure was the one that presented the best performance and quality among the agglomerative methods in the dimensions because it presented values closer to 1, this fact was more evident in the general dimension that showed 80% more efficient than the others, and the simple method, which obtained the lowest value, is not indicated, as it has low efficiency, this is due to the fact that this method evaluates the smallest dissimilarity between the objects studied. The CA obtained in this research (0.99) was higher than the study by Crispim et al (2020), in which he obtained CA = 0.94 and equal to that obtained by Roth et al (2016), with CA = 0.99. Thus, the results indicate that this technique is the most appropriate to be used in the database related to sustainability indicators for the municipalities.…”
Section: Resultscontrasting
confidence: 76%
“…The need for normalization in the grouping method is related to the different scales and measures of the indicators, directly influencing the final result. Crispim et al (2020) addressed in their study that the measurement units after standardization have similar weights. Thus, the Range method was chosen for the normalization of the indicators, making the indicator vary between 0 and 1 (Equation ): Y=Xmínitalicamp where, Y is the value obtained through the range method; X is the value of the observed variable; min is the minimum of the observed variable; amp is the total amplitude of the observed variable.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations